Upaya Mudabbir (Pembina Asrama) dalam Meningkatkan Motivasi Belajar Santri: (Studi Kasus di Pondok Pesantren Modern Arrisalah Program Internasional Slahung-Ponorogo) - Abdul Rohman (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2020)
Reason or cause students enter to Pondok Pesantren Modern Arrisatu Different, it leads to the motivation of learning a student with a different students as well, so that Mudabbir (boarder) must be really creative in Implement strategies, ways or efforts to motivate students in learning to improve students ' academic achievements. The results showed that the efforts that have been done mudabbir in improving the motivation to learn students is quite varied and good. This is evidenced by some of the efforts that Mudabbir has done in improving the motivation to learn students one Shigor class is providing intense guidance and direction individually and in groups, providing support and encouragement, providing Counsel or spiritual circumchations after the prayer, providing supervision when students study in dormitories, forming a study group and giving reward and punishment, reward in the form of praise and prizes while punishment in the form of memorizing vocabulary, Short letters, daily prayers, push up, cleaning the dorm environment, reading the quran after Asar prayer for one week and fines.